Clinical Characteristics and Treatment Outcomes of Colorectal Cancer in Jordan, a Resource-Restricted Country - Hikmat Abdel-Razeq; Maha Barbar; Sarah Abdel-Razeq; Fawzi Abuhijla; Issa Mohamad; Kamal Al-Rabi; Akram Al-Ibraheem; Hazem Hammad; Asem Mansour (JCO Global Oncology)
PURPOSEColorectal cancer is the second most prevalent cancer in Jordan and remains the second leading cause of cancer-related deaths in both men and women. This manuscript aims to explore the situation of colorectal cancer in Jordan, a resource-restricted country, and provide insights into clinical presentation and treatment outcomes.MATERIALS AND METHODSWe reviewed all reports from the Jordan Cancer Registry over the past 20 years. Treatment outcome data were obtained from the King Hussein Cancer Center (KHCC) registry since its inception in 2006 until August 2022. Overall survival (OS) was reported for the whole group and stratified by disease stage. Age-standardized incidence rates (ASIR) and mortality estimates were obtained from the latest GLOBOCAN reports.RESULTSDuring the study period, a total of 3,424 patients from the KHCC cancer registry were included in this analysis. Only a minority of the patients were diagnosed with early-stage disease, with 132 (3.9%) patients at stage I and 589 (17.2%) at stage II, whereas the majority presented with stage III (n = 1,383, 40.4%) and stage IV (1,131, 33.0%) disease. After a median follow-up of 49 months, the 5-year OS for the whole group was 53.9% (95% CI, 52.0% to 55.8%) and varied by disease stage; 87.7% (95% CI, 80.3% to 93.5%) for stage I, 84.7% (95% CI, 81.3% to 87.9%) for stage II, 69.9% (95% CI, 67.0% to 72.8%) for stage 3, and only 14.5% (95% CI, 12.2% to 16.9%) for patients with stage IV disease, P < .0001.CONCLUSIONOne third of all patients with colorectal cancer are diagnosed with metastatic disease, which explains the lower survival rates observed compared with Western countries. Programs and initiatives focused on the prevention and early detection of colorectal cancer should be a national priority.